2001
DOI: 10.1038/modpathol.3880456
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Carcinoma of the Breast: p53 Analysis Identified the Same Point Mutation in the Three Histologic Components

Abstract: A rare case of metaplastic carcinoma of the breast with both squamous metaplasia and cartilaginous metaplasia was reported. Histologically, the neoplasm revealed complex features, which were consisting of invasive ductal carcinoma, squamous carcinomatous component and chondrosarcomatoid component. Gradual transition of each component was recognized microscopically. p53 mutation analysis disclosed the same point mutation in three histologically different components, but not in the normal epithelium. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…44 However, in mixed mesenchymal breast tumors, reports on unequivocal mesenchymal lineages are numerous including chondroid and osteogenic differentiation. 45,46 That it really represents metaplasia (the divergent hypothesis) instead of a multiclonal tumor (the convergent hypothesis) has become increasingly clear based on the numerous studies of genetic markers in microdissected cells from within different compartments of the tissue. 46,47 The criteria in the present study used to categorize the cells as myofibroblastic were a fibroblastoid morphology, expression of the mesenchymal markers Thy-1 and vimentin, and most importantly the concomitant loss of keratins in some of the cells expressing ␣-sm actin.…”
Section: Discussionmentioning
confidence: 99%
“…44 However, in mixed mesenchymal breast tumors, reports on unequivocal mesenchymal lineages are numerous including chondroid and osteogenic differentiation. 45,46 That it really represents metaplasia (the divergent hypothesis) instead of a multiclonal tumor (the convergent hypothesis) has become increasingly clear based on the numerous studies of genetic markers in microdissected cells from within different compartments of the tissue. 46,47 The criteria in the present study used to categorize the cells as myofibroblastic were a fibroblastoid morphology, expression of the mesenchymal markers Thy-1 and vimentin, and most importantly the concomitant loss of keratins in some of the cells expressing ␣-sm actin.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypic alterations represent the expression of genotypic and molecular properties not present in normal mammary glandular cells, and in benign as well as some malignant conditions they are likely to be the result of de-repression of the normally coded molecular mechanisms responsible for the epithelial phenotype rather than histogenesis [11,12,13]. In support of this, some authors have demonstrated that basal-like BC may arise from luminal progenitor cells [14].…”
Section: Heterogeneity: Notions From Morphologymentioning
confidence: 74%
“…Mammary glandular cells show a high degree of phenotypic plasticity, which can be appreciated in both benign and malignant conditions [11,12,13]. These phenotypic alterations represent the expression of genotypic and molecular properties not present in normal mammary glandular cells, and in benign as well as some malignant conditions they are likely to be the result of de-repression of the normally coded molecular mechanisms responsible for the epithelial phenotype rather than histogenesis [11,12,13].…”
Section: Heterogeneity: Notions From Morphologymentioning
confidence: 99%
“…The most explicable theory regarding the histogenesis of the metaplastic components is through transformation of myoepithelial cells. Wang et al 4 in their research consider that the tumor may have been derived from the same duct progenitor cells, and that these cells still remain multipotential after a p53 point mutation. The lineage of cells bound for luminal cells differentiate to ductal carcinoma, cells for basal cells differentiate to squamous carcinomatous element, and cells for myoepithelial cells differentiate to chondrosarcomatoid element.…”
Section: Discussionmentioning
confidence: 98%
“…The lineage of cells bound for luminal cells differentiate to ductal carcinoma, cells for basal cells differentiate to squamous carcinomatous element, and cells for myoepithelial cells differentiate to chondrosarcomatoid element. 4 Recent studies sug- gest that many cases of MC are of myoepithelial origin. Koker and Kleer suggested that p63, a sensitive and specific marker of myoepithelium, is expressed in most MCs of the breast.…”
Section: Discussionmentioning
confidence: 99%